In-Vitro Anticancer Activity of Chemical Constituents from Etlingera alba Poulsen against Triple Negative Breast Cancer and in silico Approaches towards Matrix metalloproteinase-1 Inhibition - W. Wahyuni; Ajeng Diantini; Mohammad Ghozali; Anas Subarnas; Euis Julaeha; Riezki Amalia; Adryan Fristiohady; Andini Sundowo; Sofa Fajriah; Yuni Elsa Hadisaputri; Raden Maya Febrianti; Fauzia Azzahra; Agung W.M. Yodha; I. Sahidin (Indonesian Journal of Science and Technology, 2022)
Etlingera alba (EA) is one of the endemic plants grown in Sulawesi. We determined the cytotoxic and anti-metastatic activity of isolates obtained from EA rhizome extract. IC50 value for 1,7-diphenyl-6-heptene-3-one, sitostenone, sinapyl alcohol diacetate, and sinapyl alcohol acetate were 134.59; 170 ; 128.11; and 161.96 μg/mL, respectively. The compounds also had anti-migration activity. 200-μg/mL Sitostenon exhibited the lowest migration rate (3.32%). The free bond energies of sitostenon, 1,7-diphenyl-6-heptene-3-one, sinapyl alcohol acetate, and sinapyl alcohol diacetate were -11.81; -8.25; -6.64; and -6.28 kcal/mol, respectively. All compounds were more effective in stabilizing the Matrix metalloproteinase 1 complex. Isolation from EA rhizomes have the potential to be developed as anti-metastatic for Triple-Negative Breast Cancer.